Decarbonizing the energy supply one pandemic at a time. (December 2021) - Russo, M.A.; Ruivo, L.; Carvalho, D.; Martins, N.; Monteiro, A.
Abstract: This study explores different energy consumption vectors during the first year of the COVID-19 pandemic in Portugal. Most of the workforce started working from home and resource consumption significantly shifted towards the domestic sector. The ensuing confinement protocols caused a shift in everyday life, which in turn significantly altered the energy supply and demand landscape. This event, although catastrophic in terms of loss of human life and economic development, can provide us with valuable data to study the potential of new strategies to achieve EU 2050 Energy goals. It was investigated whether the pandemic has opened a path and provided us with a partial answer to decarbonization in the form of home office practices as a possible energy efficiency measure. The present study shows that, in Portugal, there was a 15.7% reduction of primary energy consumption (accounting for electricity, natural gas and transport fuels) compared to 2019. The data suggest that actions targeting reduced mobility, such as home office practices and the decentralization of the workforce, could be a relevant energy efficiency measure. Highlights: COVID19 confinement measures disrupted supply chain and worker mobility during 2020. There was a 15.7% reduction of primary energy consumption due to the pandemic. Results suggest home office practices could be a viable energy efficiency measure. Remote workers could decrease carbon dependency of the transport sector.